Religious Pluralism in Indonesia: A Critical Analysis of Indonesian Muslim Interpretations - Muhammad, (Afkar: Jurnal Akidah dan Pemikiran Islam, 2025)
Indonesia has the largest Muslim population in the world and is home to a rich diversity of cultures and religions. The country, as stated in its constitution, recognises five religions and one belief system. Consequently, themes of tolerance, moderation, and religious pluralism are of great interest not only to Indonesian scholars but also to those from abroad. Indonesian Muslim scholars hold diverse perspectives on the concept of religious pluralism. Some interpret it as an expression of tolerance and peaceful coexistence. In contrast, others adopt a more controversial view, asserting that all religions are equally valid and that no single truth is absolute. Proponents of this latter interpretation often cite Quranic verses that they claim recognise the legitimacy of all religions, not solely Islam, as conveyed through the teachings of the Prophet Muhammad (PBUH). This article critically examines the arguments presented by proponents of religious pluralism in Indonesia, with a focus on the Quranic verses they frequently cite. Employing a method of descriptive criticism, the analysis reveals that these interpretations are often based on misunderstandings and misreadings of the verses in question. It further suggests that their readings are frequently shaped by external influences such as political agendas, personal interests, the pursuit of public recognition, and alignment with large-scale ideological projects. A key issue lies in their predominantly textual and Western-influenced approach, which lacks methodological innovation and fails to engage deeply with the exegetical tradition. Additionally, significant errors are found in their use of supporting concepts, such as their invocation of sunnatullāh to explain human diversity, and their interpretation of the term al-Islām in the Qur’an.